Aglomerados binários da Pequena Nuvem de Magalhães: um estudo fotométrico de casos - Ariana Franca Clavia (2016)
A sample of 10 star clusters of the Small Magellanic Cloud, observed with the 4m SOAR telescope using B and V filters, was reduced and analized. The sample contains pairs of clusters and systems that appear to be mergers, that is evidenced by their distorted structures revealed by the built density maps . By fitting isochones on their color-magnitude diagram, we determined reddening, age and metallicity. We estimated the clusters central density, core radius and tidal radius by fitting King models over their stellar density profile. Disturbances of the density profile are interpreted as evidence of interation or originated in the process of the formation cluster. Other evidences of interation are the distance between the components of the pair and the difference of age between them. Our analisys indicated that the pairs IC 1612/H 86-186, with ages 102 e 41Myears respectively and IC 1641/NGC 422,with ages 126 e 708Myears respectively, can be physical binary due to their closeness and the structures highlighted in the density map. In the case of pairs K50/BS 123, which ages are 16 e 25Myears respectively, and NGC376/BS 114, with ages 18 e 398Myears respectively, there are no evidence of interation in the density maps. However, K50 and NGC376 present density profile with desviations from King model, suggesting that they can be systems in process of merging or in dissolution after the gas loss associated with their initial phase of evolution. IC 1611 is a candidate to be merger but he didnt present characteristics thatsupport this hypothesis. As a control sample analysis results we use the same methods of analysis in BS196, the results agreed with the literature.